Development of a real-time PCR protocol requiring minimal handling for detection of vancomycin-resistant enterococci with the fully automated BD max system - Dalpke, Alexander; Hofko, Marjeta; Zimmermann, Stefan (Journal of clinical microbiology, 2016)
Vancomycin-resistant enterococci (VRE) are an important cause of health care-associated infections, resulting in significant mortality and a significant economic burden in hospitals. Active surveillance for at-risk populations contributes to the prevention of infections with VRE. The availability of a combination of automation and molecular detection procedures for rapid screening would be beneficial. Here, we report on the development of a laboratory-developed PCR for detection of VRE which runs on the fully automated Becton Dickinson (BD) Max platform, which combines DNA extraction, PCR setup, and real-time PCR amplification. We evaluated two protocols: one using a liquid master mix and the other employing commercially ordered dry-down reagents. The BD Max VRE PCR was evaluated in two rounds with 86 and 61 rectal elution swab (eSwab) samples, and the results were compared to the culture results. The sensitivities of the different PCR formats were 84 to 100% for vanA and 83.7 to 100% for vanB; specificities were 96.8 to 100% for vanA and 81.8 to 97% for vanB. The use of dry-down reagents and the ExK DNA-2 kit for extraction showed that the samples were less inhibited (3.3%) than they were by the use of the liquid master mix (14.8%). Adoption of a cutoff threshold cycle of 35 for discrimination of vanB-positive samples allowed an increase of specificity to 87.9%. The performance of the BD Max VRE assay equaled that of the BD GeneOhm VanR assay, which was run in parallel. The use of dry-down reagents simplifies the assay and omits any need to handle liquid PCR reagents.